Meckel Gruber syndrome - a case report - Marquess Raj; Sujata Dhanuka; Prerna Agarwal; Suresh Lakki Reddy; Sethuramalingam Vivekananthan (BMC, 2020)
Abstract Background Meckel Gruber Syndrome (MKS) is a rare autosomal recessive malformation syndrome characterized by multiple congenital anomalies ultimately leading to the death of fetus in utero or shortly after birth. It is characterized by classical triad of occipital encephalocele, infantile polycystic kidneys and postaxial polydactyly. Diagnosis of MKS is made on the basis of ultrasonography, gross morphology & histopathological findings. Here, we describe a case of MKS presenting with the classical triad. Case presentation A 25 year old lady presented with missed abortion at 17 weeks of gestation on her first conception. There was no history of previous fetal demise or any congenital anomaly. History of consanguineous marriage was not present. Ultra sonogram revealed death of the fetus in utero. Planned termination of pregnancy was performed & the products of conception were sent for study to the laboratory for autopsy, histopathological examination & genetic studies. Conclusion Rare genetic anomalies can present with missed abortion & an understanding of the same is important considering the clinical as well as psychological strain it can have on the pregnant mother. The case moreover should be reported for it being a genetic anomaly which results in death at a young age & also for its historical value.